Design, Synthesis And Antimicrobial Activity Of 2-Mercaptobenzimidazole Derivatives - GIGANI YASEEN; JADHAV SUDHAKAR (International Journal of Pharma and Bio Sciences, 2010)
Dihydrofolate reductase (DHFR) is the important target for antimicrobial drugs belonging to the class of antimetabolites as the enzyme plays important role in the de novo purine synthesis. Since 2-mercaptobenzimidazole(2MBI) shares structural similarity with purine nucleotides, We here report the in silico screening to obtain best fit molecules as DHFR inhibitors, synthesis of some ‘best fit’ 2MBI derivatives (Mannich bases) and their in vitro antimicrobial assay using paper disc method. The structures of these molecules were elucidated by Infrared. These compounds were then subjected for in vitro antimicrobial activity against gram +ve and gram -ve bacteria using Ciprofloxacin as standard at concentrations of 50ug/ml, 100ug/ml and 200ug/ml. Some of the compounds show satisfactory activity at 200ug/ml.